Avaliação do torque dos braquetes dos incisivos superiores e inferiores da terapia bioprogressiva de Ricketts - Gomes Filho, Wander Vicente (2007)
Technological advance has provided improvement in materials, allowing professionals to obtain better precision in the results of their treatments. In Orthodontics, the possibility of making use of pre-adjusted brackets represents one of these advances. The aim of this study was to assess the precision of the torque on pre-adjusted maxillary and mandibular incisor brackets, prescribed by the Ricketts Bioprogressive Therapy. Three hundred and sixty brackets of commercial brands on the Brazilian market were assessed: Abzil and Morelli, manufactured in Brazil, Dentaurum, Forestadent, GAC and Rocky Mountain Orthodontics (RMO), imported brands. A Zeiss brand, model DSM 940A scanning electronic microscope (SEM) was used, which is a versatile instrument routinely used for analyzing solid material microstructures. The images obtained were analyzed using AutoCAD 2000 software. The precision of the torque on the brackets was measured by means of the angles of the incisor wall (IWA) and of the cervical wall (CWA), measured at the intersection of the bracket base line with the internal lateral, incisor and cervical lines, respectively of the slots. The statistical results demonstrated that the mean values of the maxillary central incisor bracket torque as regards the IWA were statistically similar to the value prescribed for the Forestadent, Morelli and RMO brands. With regard to the CWA, the prescribed value differed statistically from the means of all the brands assessed. With regard to the maxillary lateral incisor brackets, the mean IWA value of the Dentaurum, Forestadent and RMO brands were shown to be statistically in agreement with the value prescribed by the technique. The CWA angle was significantly similar to the prescribed value for the Morelli and RMO brands. For the mandibular incisor brackets, the IWA angle was found to be statistically in agreement with the prescribed value for the Forestadent, Morelli and RMO brands. Whereas the CWA differed significantly from the prescribed value for all the studied brands. It was concluded that there is notable divergence in the fabricated torque of the various brands in comparison with that prescribed by the studied technique; however, this difference was lowest for the RMO brand brackets, in which only the CWA angles of the maxillary and mandibular central incisors were in disagreement with the prescription. The Abzil and GAC brands were shown to be divergent from the prescribed torque in all the angles evaluated.